2015
DOI: 10.1111/pde.12632
|View full text |Cite
|
Sign up to set email alerts
|

Role of Narrowband Ultraviolet B Phototherapy in the Treatment of Childhood Psoriasis in Asian Children

Abstract: Narrowband ultraviolet B (NBUVB) phototherapy is a well-established treatment modality for psoriasis. We performed a retrospective analysis of children of East Asian descent with psoriasis treated with NBUVB phototherapy at the National Skin Centre, Singapore, over a 5-year period between 2004 and 2008 and found that NBUVB phototherapy is safe and effective for the treatment of psoriasis in children of East Asian descent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…In 2011, a retrospective study in pediatric psoriasis patients showed complete clearance in 51% and a good response (at least 75% improvement) in 41% of the subjects through a mean treatment duration of 3.3 months [ 20 ]. Recently, Wong et al performed a retrospective study on 12 pediatric psoriasis patients treated with NB-UVB, also performing a thorough review of the literature, and concluded that this type of phototherapy is a safe and effective treatment for childhood psoriasis and should be considered in children with suboptimal response to topical therapy [ 21 ]. Indeed, there are several published case series in the literature attesting to the efficacy of UVB phototherapy, in particular NB-UVB phototherapy, in treating plaque and guttate psoriasis in children aged 2–18 years, with the majority of patients achieving a moderate to significant response or almost complete to total remission over an average of 25–34 treatments, with one study reporting a mean duration of remission of 8 months [ 16 , 20 , 22 25 ].…”
Section: Phototherapymentioning
confidence: 99%
“…In 2011, a retrospective study in pediatric psoriasis patients showed complete clearance in 51% and a good response (at least 75% improvement) in 41% of the subjects through a mean treatment duration of 3.3 months [ 20 ]. Recently, Wong et al performed a retrospective study on 12 pediatric psoriasis patients treated with NB-UVB, also performing a thorough review of the literature, and concluded that this type of phototherapy is a safe and effective treatment for childhood psoriasis and should be considered in children with suboptimal response to topical therapy [ 21 ]. Indeed, there are several published case series in the literature attesting to the efficacy of UVB phototherapy, in particular NB-UVB phototherapy, in treating plaque and guttate psoriasis in children aged 2–18 years, with the majority of patients achieving a moderate to significant response or almost complete to total remission over an average of 25–34 treatments, with one study reporting a mean duration of remission of 8 months [ 16 , 20 , 22 25 ].…”
Section: Phototherapymentioning
confidence: 99%
“…NB-UVB with a peak at 311 nm, which is considered to be more effective than broadband UVB, has been widely used in dermatological phototherapy. In particular, it is a well-established treatment modality for psoriasis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eleven studies reported on the efficacy of phototherapy in children with plaque and guttate psoriasis (364 patients aged 3 to 17). [54][55][56][57][58][59][60][61][62][63][64] NB-UVB treatment was used in all studies, whereas the retrospective review by Ersoy-Evans et al 62 also included psoralen-UVA (PUVA) and regular UVB. In this study, the authors concluded that the efficacy of NB-UVB and UVB treatment were equally more effective with 75% less clearance achieved in 93% of the patients compared to PUVA treatment with <75% clearance achieved in 83%; the assessment score was not specified.…”
Section: Phototherapymentioning
confidence: 99%
“…Phototherapy was effective overall in a large number of participants, although erythema was a common adverse event observed in 8/11 studies. [56][57][58][60][61][62][63][64] Two patients discontinued treatment in one study due to the development of erythroderma following NB-UVB treatment. 54 It is notable that topical treatment was used or allowed in 6/ 11 studies, 58,60,[62][63][64] while the clinical trial by Tan et al 56 allowed both topical and systemic treatment.…”
Section: Phototherapymentioning
confidence: 99%